INTERVENSI REGULASI EMOSI OLEH GURU PENDAMPING KHUSUS (GPK) PADA ANAK AUTISM SPECTRUM DISORDER (ASD)DI HOMESCHOOLING SUKACITA BANJARMASIN - Munawwaroh Munawwaroh; Miftahul Aula Sa’adah (ADIBA : JOURNAL OF EDUCATION, 2025)
Emotions of various types arise in self-awareness as responses to various things. Intense emotional feelings are often an important part of every individual's consciousness. Children need to develop ways to manage their emotions in order to build better social-emotional skills. This is important not only for normal children, but also for children with special needs. For children, this ability is the foundation for building social relationships, improving psychological well-being, and facing daily challenges. Children with Autism Spectrum Disorder (ASD) often face obstacles in regulating their emotions, which can trigger challenging behaviours such as tantrums, aggression, or withdrawal. This condition requires targeted interventions to help children manage their emotions adaptively. Special needs teachers (GPK) not only play a role in academic aspects but also as facilitators of children's emotional development. This study aims to describe the stages of emotional regulation intervention carried out by special assistant teachers (GPK) on children with ASD at Homeschooling Sukacita Banjarmasin, as well as to identify the supporting and inhibiting factors. This study uses a qualitative approach with a case study method. Data were obtained through interviews, observations, and documentation. The results show that emotional regulation intervention is carried out through five stages according to Gross, namely situation selection, situation modification, attention diversion, cognitive change, and response modulation. The implementation included breathing exercises, providing space to calm down, simple instructions, and individual strategies according to the child's needs. This intervention had a positive impact, as shown by a reduction in the frequency of tantrums, an increase in the ability to delay gratification, and an improvement in emotional expression skills. Supporting factors include parental involvement, the competence of special support teachers (GPK), and a conducive learning environment, while obstacles include limited resources, differences in children's characteristics, and unstable emotional conditions.